GP Letter Writing in Colorectal Cancer: A Qualitative Study - Jiwa, Moyez; Burr, Jennifer (Librapharm, 2002)
Background: The usual mode of communication with the specialist in the UK is a referral letter. Letters now primarily document the GPs' concerns for the patient and are no longer required to persuade the specialist to offer an appointment. The content of referral letters from GPs has failed to satisfy specialists responding to a series of surveys. Evidence suggests that GPs who improve their letters to specialists also refer more cases with significant pathology.Aims: The aims of this research are to explore the factors that may influence GPs in writing the referral letter when consulting patients presenting with lower bowel symptoms.Methods: A convenience sample of twelve GPs was interviewed in Nottinghamshire and inner city Sheffield practices. A framework approach was utilised in the analysis of data. Data from the interviews followed the prescribed steps, including: familiarisation, identifying a thematic framework, indexing, charting and mapping, and interpretation.Results: The thematic framework reflected four major themes. These were: (1) the nature and content of referral letters, (2) knowledge about colorectal cancer, (3) issues relating to the quality of referral letters in colorectal cases and (4) factors that effect the use of guidelines for referral.Conclusions: GPs only have very short consultations in which to address many and complex issues. Pre-referral assessment in colorectal cases includes intimate examination of the patient. Therefore the writing of the letter of referral is often postponed until long after the patient has left the GP's office. Some GPs do not believe the consultant reads the letter of referral. However, GPs are keen to provide best care and welcome feedback about the quality of their letters. They acknowledge the responsibility to communicate with colleagues effectively and have differing ideas about what constitutes an adequate referral letter.